Efficacy and Safety of Omadacycline in Patients with Acute Bacterial Skin and Skin Structure Infections (ABSSSI) and High Body Mass Index or Type 2 Diabetes: A Subgroup Analysis from the OASIS Tria. (4th October 2017) - Wilcox, Mark; Cure-Bolt, Nancy; Chitra, Surya; Tzanis, Evan; McGovern, Paul
Abstract: Background: Skin infections in overweight/obese patients or patients with diabetes mellitus (DM) are common and can be associated with poor outcomes. Omadacycline (OMC) is a first-in-class aminomethylcycline. Intravenous (IV)-to-once-daily oral OMC demonstrated non-inferiority to IV-to-twice-daily oral linezolid (LZD) in the phase 3 ABSSSI study, OASIS. Here, we report the efficacy and safety of OMC vs. LZD in patients with high body mass index (BMI) or type 2 DM from OASIS in a post-hoc analysis. Methods: 655 adult patients were randomized 1:1 to OMC 100 mg IV q12h × 2  doses then 100 mg IV q24h, or to LZD 600 mg IV q12h. After ≥ 3 days' IV therapy, patients could transition to oral OMC 300 mg q24h or oral LZD 600 mg q12h. Total treatment duration was 7–14 days. Primary endpoint was early clinical response (ECR) assessed at 48–72 hours in the modified intent to treat (mITT) population. Secondary endpoints were clinical response at post-treatment evaluation (PTE) in the mITT and clinically evaluable (CE) populations. Safety was assessed based on adverse events (AEs), vital signs, and laboratory tests. 228 patients had a normal BMI (BMI <25); 417 had a high BMI (BMI ≥25). Of those with a high BMI, 225 were overweight (25 ≤ BMI <30) and 192 were obese (BMI ≥30). 59 patients had a medical history of DM. Results: ECR rates with OMC were similar for normal and high BMI patients. At PTE, OMC-treated patients showed higher clinical success vs. LZD-treated patients across most subgroups. At PTE, OMC-treated DM patients showed higher clinical success vs. LZD-treated DM patients. None of the OMC vs. LZD differences were significant. Nausea and vomiting were less frequent in patients treated with OMC vs. LZD across all subgroups studied. Conclusion: IV-to-once-daily oral OMC was effective and well-tolerated for treating ABSSSI irrespective of BMI or DM status. Disclosures: N. Cure-Bolt, Paratek Pharmaceuticals: Employee and Shareholder, Salary; S. Chitra, Paratek Pharmaceuticals: Employee and Shareholder, Salary;  E. Tzanis, Paratek Pharmaceuticals: Employee and Shareholder, Salary; P. McGovern, Paratek Pharmaceuticals: Employee and Shareholder, Salary.